Molecular diagnosis of bird-mediated pest consumption in tropical farmland - Karp, Daniel S (Springer International Publishing, 2014)
Biodiversity loss will likely have surprising and dramatic consequences for human wellbeing. Identifying species that benefit society represents a critical first step towards predicting the consequences of biodiversity loss. Though natural predators prevent billions of dollars in agricultural pest damage annually, characterizing which predators consume pests has proven challenging. Emerging molecular techniques may illuminate these interactions. In the countryside of Costa Rica, we identified avian predators of coffee’s most damaging insect pest, the coffee berry borer beetle (Coleoptera:Scolytidae Hypothenemus hampeii), by assaying 1430 fecal samples of 108 bird species for borer DNA. While feeding trials confirmed the efficacy of our approach, detection rates were low. Nevertheless, we identified six species that consume the borer. These species had narrow diet breadths, thin bills, and short wings; traits shared with borer predators in other systems. Borer predators were not threatened; therefore, safeguarding pest control necessitates managing species beyond those at risk of regional extinction by maintaining populations in farmland habitats. Generally, our results demonstrate potential for pairing molecular methods with ecological analyses to yield novel insights into species interactions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/2193-1801-3-630) contains supplementary material, which is available to authorized users.